NHC-Catalysed, chemoselective crossed-acyloin reactions - GUNDALA , SIVAJI; CONNON, STEPHEN (My University, 2012)
It has been shown for the first time that relatively electron deficient triazolium pre-catalysts promote (at low loadings in the presence of base) highly chemoselective crossed acyloin condensation reactions between aldehydes and α-ketoesters to afford densely functionalized products incorporating a quaternary stereocentre of considerable synthetic potential. Hydroacylation pathways which have hitherto been dominant in these reactions can be completely avoided. The scope of the process is extraordinarily broad with respect to both coupling partners, and a preliminary study has established the principle that a high degree of stereochemical control over the reaction can also be exercised via the use of a chiral NHC precursor. It has also been shown for the first time that coupling of benzyl α-ketoesters with aldehydes followed by acylation and simple hydrogenolysis furnishes a product formally derived from the chemoselective 1[thin space (1/6-em)]:[thin space (1/6-em)]1 coupling of two different aliphatic aldehydes in high yield with absolute control over which coupling partner behaves as the acyl-anion equivalent.
PUBLISHED
Keywords: Chemistry